Effect of high concentration granients on hydrodynamic dispersion - Sarıoğlu, Murat Savaş. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
The hydrodynamic dispersion of contaminants in the subsurface is commonly described by Fick's Law which expresses the dispersive mass flux as a linear function of the concentration gradient with a constant dispersion coefficient. However, recent research has shown that the relationship deviates from linearity under high concentration gradient conditions. Although, several modifications of Fick’s Law have been proposed in order to account for this deviation under specific conditions, there is still not a broadly accepted tool for modeling the dispersion flux in real environmental applications. This study investigates the effect of high concentration gradients on hydrodynamic dispersion for experimental conditions beyond those considered in the literature, namely, existence of multiple species and low velocity conditions similar to those commonly encountered in natural subsurface systems. In order to test alternative dispersion models and determine transport parameters for subsequent model applications, three sets of stable miscible displacement experiments were conducted in two different types of porous media: (i) tracer experiments, (ii) brine experiments with varying flow rates and concentration gradients, (iii) mixture experiments where brine was mixed with a low concentration contaminant. The laboratory experiments showed that dispersive behavior deviates from Fickian Theory when high density gradients exist, for all high and low concentration solute components in groundwater. A numerical model was developed and validated using the experimental results. The model was then used to perform Monte-Carlo simulations of a transport problem where high concentration gradients exist along with heterogeneity in hydrogeological parameters. Simulation results suggested that non-Fickian behavior may significantly affect observations of transport, subsequent parameter estimations and potential effectiveness of groundwater remediation activities.
Keywords: Hydrodynamics -- Mathematical models.; Dispersion -- Mathematical models.